A Clarification of the Terms Dakhma and Astodān on the Basis of Literary Records and Archeological Research in Fars Province. - Doroodi, Mojtaba; Hajiani, Farrokh (Journal of Persianate Studies, 2021)
The terms dakhma (open-air tomb) and astodān (ossuary) are often used interchangeably despite the fact that they refer to two distinct structures with different meanings in pre-Islamic Iranian burial practices. The present study explores the differences between the two structures, along with burial-related terms used by ancient Persians, by examining ancient and medieval Iranian manuscripts and by conducting a field study of surviving artifacts from ancient times. The results show that dakhma (or dakhmagāh) was a general term referring to the entire burial site and its constituent elements—as opposed to the specific astodān. Both of these structures should be differentiated from small hollowed ledges on the edges or surfaces of mountains, which were engraved as late as the early Islamic period (seventh to ninth centuries), even though the terms dakhma and astodān appear in their inscriptions. Although the latter have led some scholars to conflate the terms, the present study finds that these small stone structures and hollows are neither dakhma nor astodān , but rather served as a symbolic memorial to the departed. Furthermore, other burial-related structures in the environs of the dakhma , including mortar-shaped hollowed stones (sang-āb s) and cascade-like stone grooves (called sor-sor-e hāy-e sangi), which have received scant attention, can be traced back to Zoroastrian rituals in Avestan texts and point to the presence of a dakhma. Finally, the present field study, which explored ancient burial sites in the Marvdasht plain in Fars Province, includes unique information and details that are presented here for the first time.